Efficient atom and step economic (EASE) synthesis of the "smart drug" Modafinil. Issue 3 (9th December 2016) - Maurya, Shivam; Yadav, Dhiraj; Pratap, Kemant; Kumar, Atul
Abstract : We developed a post-sulfoxidation protocol for the synthesis of Modafinil that exhibits improved sustainability credentials, utilizing the recyclable heterogeneous catalyst Nafion-H. Abstract : Modafinil (2-[(diphenylmethyl)sulfinyl]acetamide, MOD) is a key psychostimulant drug used for the treatment of narcolepsy and other sleep disorders that has a very low addiction liability. Recently, MOD has been clinically investigated for the treatment of cocaine addiction and used by astronauts in long-term space missions. We have developed a synthetic strategy for "smart drug" Modafinil. An efficient atom and step economic (EASE) synthesis has been carried out by the direct reaction of benzhydrol and 2-mercaptoacetamide using the recyclable heterogeneous catalyst Nafion-H along with post-sulfoxidation. This protocol exhibits improved sustainability credentials. We have also developed a superior pre-sulfoxidation approach for the synthesis of Modafinil.